Empirical metronidazole for patients with severe bacterial infection: protocol for a systematic review. Issue 5 (8th March 2018) - Petersen, M. W.; Perner, A.; Bahador, M.; Sjövall, F.; Møller, M. H.
Abstract : Introduction: Anaerobic bacteria are believed to be common pathogens in severe infections. Yet, they are difficult to culture and consequently often unrecognised in clinical infections. Metronidazole is often used empirically for potential anaerobic infections, as the resistance to metronidazole is low. However, disadvantages of metronidazole use exist, including drug interactions, side effects and economical expenses. Currently, the balance between the benefits and harms of empirical metronidazole for severe bacterial infections is unknown. We aim to assess patient‐important benefits and harms of empirical metronidazole vs. placebo or no treatment in adult patients with severe bacterial infection of any origin in a systematic review of randomised clinical trials with meta‐analysis and trial sequential analysis. Methods and analysis: This protocol provides details on the planned systematic review, which will be prepared according to the Preferred Reporting Items for Systematic Reviews and Meta‐analyses (PRISMA) statement, the Cochrane Handbook, and the Grading of Recommendations, Assessment, Development and Evaluation (GRADE) criteria. The primary outcome is all‐cause mortality. Secondary outcomes include adverse events, secondary infections, use of life support, antibiotic resistance and hospital length of stay. We will conduct conventional meta‐analyses, including predefined subgroup‐ and sensitivity analyses. Additionally, we will assess the risk of random errors by trial sequential analysis. Ethics and dissemination: Ethical approval is not needed, as the outlined review exclusively will include previously published data. We aim to publish in an international, peer‐reviewed journal.